2017
DOI: 10.1016/j.psychres.2017.07.025
|View full text |Cite
|
Sign up to set email alerts
|

Maternal infection and stress during pregnancy and depressive symptoms in adolescent offspring

Abstract: Maternal infection during pregnancy has been linked to increased risk of offspring depression. Additionally, maternal stress during pregnancy has been consistently linked with adverse offspring outcomes associated with depression. Relatedly, stress has been associated with increased risk of infection; however no study has investigated stress-infection interactions during pregnancy and risk for offspring depression. Participants were drawn from the Child Health and Development Study (CHDS), a prospective, longi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 117 publications
(146 reference statements)
2
45
0
1
Order By: Relevance
“…A few studies have investigated the lifetime risk of depression for the child after exposure to particular infections, but they have yielded mixed results. 43,44 Although vulnerable to possible loss to follow-up bias, our study provides suggestive evidence for a fetal origin for depression, with separate support using suicide data from the Swedish National Death Registry. Although little is known about the scientific basis to link aberrant fetal neurodevelopment with subsequent risk for depression, infection and inflammation in the pregnant mouse lead to alterations in placental serotonin production and dysgenesis of serotonergic neurons in the fetal brain.…”
Section: Discussionsupporting
confidence: 52%
“…A few studies have investigated the lifetime risk of depression for the child after exposure to particular infections, but they have yielded mixed results. 43,44 Although vulnerable to possible loss to follow-up bias, our study provides suggestive evidence for a fetal origin for depression, with separate support using suicide data from the Swedish National Death Registry. Although little is known about the scientific basis to link aberrant fetal neurodevelopment with subsequent risk for depression, infection and inflammation in the pregnant mouse lead to alterations in placental serotonin production and dysgenesis of serotonergic neurons in the fetal brain.…”
Section: Discussionsupporting
confidence: 52%
“…infection to modulate offspring neurodevelopmental outcome. For example concurrent infection and stress during the second trimester result in a higher adolescent depression score in offspring then either alone [ 101 ].…”
Section: Maternal Stressmentioning
confidence: 99%
“…This study suggests inflammation in the placenta may contribute to sex differences observed in offspring following PNMS [47]. Moreover, we previously found that prenatal infection during the second trimester was associated with offspring depressive symptoms only if the mother also reported daily life stress [48]. These findings cumulatively support the possibility that PNMS may not only increase the likelihood of getting an infection, but also increase the vulnerability of the fetus to the damaging effects of the infection, subsequently increasing the possibility of neurodevelopmental sequelae.…”
Section: Infection and Inflammationmentioning
confidence: 61%